2012
DOI: 10.1159/000339132
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted MRI of the Testis in Hydrocele: A Pilot Study

Abstract: Objective: To investigate the effects of increased pressure due to the accumulated fluid around testis in hydrocele on testis diffusion and whether this effect (if any) is correlated with the amount of fluid and duration of hydrocele. Patients and Method: 49 patients with unilateral hydrocele were evaluated by magnetic resonance diffusion-weighted imaging. Results: In the study group, while the apparent diffusion coefficient (ADC) values of the testicles with hydrocele differed significantly before and 3 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…Maki et al [5] have observed a reduction in the ADC values of patients with testis torsion and obtained an 82% accuracy with DWI. Gulum et al [16] have reported reduced ADC values due to the ischemia and the fibrosis in patients with hydrocele.…”
Section: Discussionmentioning
confidence: 98%
“…Maki et al [5] have observed a reduction in the ADC values of patients with testis torsion and obtained an 82% accuracy with DWI. Gulum et al [16] have reported reduced ADC values due to the ischemia and the fibrosis in patients with hydrocele.…”
Section: Discussionmentioning
confidence: 98%
“…They also found lower ADC values to be inversely correlated to varix size suggesting that larger varicoceles resulted in increasing testicular fibrosis [38]. Finally, Gulum et al demonstrated that unilateral hydroceles correlated with reduced ADC values in the testis on the affected side and that the size of the hydrocele also inversely correlated with ADC suggesting a negative effect on fertility from larger hydroceles [39].…”
Section: Scrotum and Testesmentioning
confidence: 98%
“…In patients with varicocele, dysfunction of the testicular vein valves leads to an increase in pressure and testicular temperature, with reflux in adrenal metabolites inducing hypoxia and oxidative stress in the testes. This leads to interstitial fibrosis and reduction in testicular volume with impairment of spermatogenesis (decreased sperm count, motility and distortion in morphology) and progressive testicular degeneration (Gulum et al, ; Hamada, Esteves, & Agarwal, ; Pastuszak & Wang, ).…”
Section: Introductionmentioning
confidence: 99%